Agro-morphological Characterization and Genetic Diversity of Similar Named Aromatic Rice (Oryza sativa L.) Landraces of Bangladesh - Islam, MZ; Akter, N; Chakrabarty, T; Bhuiya, A; Siddique, MA; Khalequzzaman, M (Bangladesh Rice Journal, 2019)
Thirty-six similar named aromatic rice landraces of Bangladesh were studied to assess the genetic variation for the agro-morphological traits through Mahalanobis D2 statistics. The landraces were grouped into four clusters, where no duplicate landrace was found. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the landraces of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the landraces within the clusters. The principal component analysis showed that the first five components with vector values > 1 contributed 76.51% of the total variations. The highest number (13) of landraces was constellated in cluster III and the lowest (3) in cluster I. The intra- and inter-cluster distances were the maximum in cluster I (0.63) and between clusters I and IV (17.13), respectively and the minimum in cluster II (0.03) and between clusters III and IV (3.86), respectively. The maximum value of inter cluster distance indicated that the landraces belonging to cluster IV were far diverged from those of cluster I. So, it is expected in our results that parent’s selection for hybridization from the clusters IV and I may give the desirable heterosis for heterotic rice hybrids. Besides, the cluster mean revealed that the crosses between the genotypes of cluster I with those of clusters IV would exhibit high heterosis for maximum good characters. Hence, yield, grain breadth, days to maturity, culm diameter, ligule length had maximum contribution towards genetic divergence. Besides, evaluation of agro-morphological characters demonstrated that the aromatic rice landraces under the present study possessed a considerable genetic diversity. Therefore, similar and duplicate named aromatic rice landraces need to be conserved in Genebank for future breeding programme. Bangladesh Rice j. 2018, 22(1): 45-56